2014
DOI: 10.1016/j.brainres.2014.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CaMKII activity in the medial prefrontal cortex is associated with cognitive dysfunction in ADHD model rats

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a heterogeneous neurobehavioral disorder accompanied by cognitive and learning deficits, which is prevalent among boys. Juvenile male stroke-prone spontaneously hypertensive rats (SHRSP) exhibit ADHD-like behaviors including cognitive deficits and represent one animal model of ADHD. Here, we define a mechanism underlying cognitive dysfunction observed in SHRSP. Acute methylphenidate (MPH: 1mg/kg, p.o.) administration to SHRSP significantly improved not only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Moreover, neither the B max nor K d of [ 3 H]MK‐801 binding in the hippocampus was significantly different between each type of rats, suggesting that NMDA receptor dysfunction in SHRSP/Ezo is PFC‐specific manner. These results are consistent with a recent report that the PFC, but not hippocampus, is likely to be responsible for AD/HD‐related behavioral deficits in SHRSP/Ezo . However, Jansen et al reported that one of the AD/HD animal models, SHR, showed the NMDA receptor subunit dysfunction in the hippocampus.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, neither the B max nor K d of [ 3 H]MK‐801 binding in the hippocampus was significantly different between each type of rats, suggesting that NMDA receptor dysfunction in SHRSP/Ezo is PFC‐specific manner. These results are consistent with a recent report that the PFC, but not hippocampus, is likely to be responsible for AD/HD‐related behavioral deficits in SHRSP/Ezo . However, Jansen et al reported that one of the AD/HD animal models, SHR, showed the NMDA receptor subunit dysfunction in the hippocampus.…”
Section: Discussionsupporting
confidence: 92%
“…To conclude, not only are these findings reminiscent of a role of CaMKIIα dysfunction in brain disorders such as Angelman syndrome (68), attention deficit hyperactivity disorder (69) and cerebral ischemia (39), they also resonate with the emerging concept that CaMKIIα is altering neuronal physiology and cognition more generally when aberrantly over-activated in the brain. In combination with earlier studies (2, 49), these results establish that distinct endogenous Aβ oligomers activate specific neuronal signaling pathways, and that mapping the specific tau changes induced by each of these Aβ toxins might provide a general template for monitoring AD progression.…”
Section: Discussionmentioning
confidence: 82%
“…Mouse cortical cultures of neurons were prepared from 14- to 15-d-old embryos as described previously (2, 69, 70) using 5×10 5 cells/dish. After 3 d in vitro (DIV), neurons were treated with 10 μM AraC to inhibit proliferation of non-neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
“…In this brain area, catecholamine neurotransmission is implicated in the coordination and integration of cues, even though they imply less complex behaviors (Arnsten, ; Jones, ). In this sense, attention is required when animals perform spatial recognition of novel environments; thus, behavioral tests evaluating exploration are indicative of PFC functional integrity, among other brain areas, such as HPC and other limbic structures (Dudchenko, ; Lalonde, ; Yabuki et al, ). The Amph‐induced working memory deficit in rodents has been previously related to oligodendrocyte altered morphology in PFC, supporting the coexistence of functional and structural alterations in this brain area after Amph exposure (Yang, Wang, Cheng, & Xu, ).…”
Section: Discussionmentioning
confidence: 99%